Power Capacity and Speed Analysis for Elevator Motors at Madani Hospital Pekanbaru - Lanisa, Vicensia; Rajagukguk , Antonius (International Journal of Electrical, Energy and Power System Engineering, 2023)
An elevator or elevator is a means of conveyance found in high-rise buildings to make it easier for people to move quickly to the desired floor. Currently, the motor that is widely used as an elevator driver is a three-phase induction motor. The output of this three-phase induction motor is in the form of torque to drive the elevator. Of course, the number of passengers carried by the elevator has a different weight so that it will affect the power and torque generated by the motor to transport these passengers. The method used in this study was to collect data in the form of data on the number of passengers and data on lift motors at Madani Hospital by observation. Then after the data is obtained, measurements and calculations are carried out to obtain the torque, power and speed of the elevator motor. The results of this study are with a passenger load of 0 kg, 196 kg, 678 kg, 891 kg and 1,122 kg, when the elevator goes up the more the number of passengers, the greater the power and torque of the motor. The magnitude of the motor mechanical torque needed to move between floors is the same, if the distance between the floors is the same. The addition of passengers does not affect the speed of the elevator motor because the elevator moves constantly.